Syneruptive incorporation of martian surface sulphur in the nakhlite lava flows revealed by S and Os isotopes and highly siderophile elements: implication for mantle sources in Mars. (1st December 2019) - Mari, N.; Riches, A.J.V.; Hallis, L.J.; Marrocchi, Y.; Villeneuve, J.; Gleissner, P.; Becker, H.; Lee, M.R.
Abstract: Martian lava flows likely acquired S-rich material from the regolith during their emplacement on the planet's surface. We investigated five of the twenty known nakhlites (Nakhla, Lafayette, Miller Range (MIL) 090032, Yamato 000593, and Yamato 000749) to determine whether these lavas show evidence of regolith assimilation, and to constrain the potential implications that this process has on chemical tracing of martian mantle source(s). To establish the proportionate influence of atmospheric, hydrothermal, and volcanic processes on nakhlite isotopic systematics we obtained in situ sulphur isotope data (Δ 33 S and δ 34 S) for sulphide grains (pyrrhotite and pyrite) in all five nakhlite samples. For Nakhla, Lafayette, and MIL 090032, these data are integrated with highly siderophile element (HSE) abundances and Os-isotope compositions, as well as textural information constrained prior to isotopic analysis. This work thereby provides the first Re-Os isotope systematics for two different nakhlites, and also the first Re-Os isotope data for martian sample for which detailed petrographic information was constrained prior to digestion. We report the largest variation in δ 34 S yet found in martian meteorites (−13.20‰ to +15.16‰). The relatively positive Δ 33 S and δ 34 S values of MIL 090032 (δ 34 S = +10.54 ± 0.09‰; Δ 33 S = −0.67 ± 0.10‰) indicate this meteorite assimilated sulphur affected by UV-photochemistry. In contrast, the strongly negative values of Lafayette (δ 34 S = −10.76 ± 0.14‰; Δ 33 S = −0.09 ± 0.12‰) are indicative of hydrothermal processes on Mars. Nakhla, Yamato 000593, and Yamato 000749 sulphides have a narrower range of sulphur isotope compositions (Δ 33 S and δ 34 S ∼ 0) that is consistent with no assimilation of martian surface materials during lava flow emplacement. Consequently we used this second group of Δ 33 S values to approximate the Δ 33 S of the nakhlite source, yielding a Δ 33 S value of −0.1‰. Nakhlite HSE patterns result from a sulphide-saturated melt where Ru-Os-Ir alloys/sulphide were likely crystallized during earlier phases of magmatic processing in Mars to result in the fractionated HSE patterns of the nakhlites. Our data, alongside a synthesis of previously published data, suggest assimilation of an enriched component to the primary nakhlite melt, potentially a late-stage crystallization cumulate from the martian magma ocean stage. In the context of this model, and within large uncertainties, our data hint at perturbation and potential decoupling of nakhlite Re-Os isotope systematics from other isotopic systems as a result of small degrees of assimilation of a regolith component with highly radiogenic 187 Os/ 188 Os.